Self Help bagi Konselor Sebaya: Studi Fenomenologi Mahasiswa Santri Pelaku Konseling Sebaya - Alfadla, Maya Tsuroya; Muslih, Mohammad; Putra, Mochammad Fachturrahman Spama; Tharmidzi, Muhammad (Institut Agama Islam Sumatera Barat, 2023)
This research seeks to explore the phenomenological experiences of Islamic boarding school students when they become peer counselors. On the one hand, he carries out professional peer counseling, but on the other hand, he also experiences a crisis or exploration as a stage of his psychological development. This research will answer how he manages psychological turmoil as a person and peer counselor. Researchers use qualitative phenomenological research which makes it possible to explore in depth the phenomenon, the subject's experience of himself, his interactions with other people, and the subject's experience of other people's experiences. Data was collected through in-depth interviews, observation, and documentation studies. Data analysis went through five stages, including; 1) Manage and prepare data; 2) Read all the data; 3) Coding; 4) Grouping/Creating themes; and 5) Conclusion and Discussion. The findings in this research are grouped into two themes as follows; 1) Problems experienced by peer counselors; and 2) Self Help method carried out by peer counselors. Self-help methods carried out by peer counselors are meditation, crying therapy, and journalizing/narrative therapies. Each self-help method also produces information about the reasons for choosing the method, how to do the self-help, time and place, and the effects caused after doing the self-help.